1995
DOI: 10.1016/0020-7292(95)80022-0
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic endometrial carcinoma after endometrial ablation

Abstract: Endometrial ablation has been recently introduced as a surgical alternative to hysterectomy for the treatment of dysfunctional uterine bleeding. The procedure itself is reasonably safe. However, if occult endometrial cancer is present before the procedure and is not detected, it may be more difficult to diagnose later. Endometrial cancer may also arise de novo from missed endometrial tissue. Two cases of endometrial cancer following endometrial ablation have been reported, but its overall incidence is unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 11 publications
0
13
2
Order By: Relevance
“…EC after endometrial ablation is a rare but possible occurrence, as described in the literature in a number of case reports [13][14][15][16][17][18][19][20][21][22]. The exact rate of EC after endometrial ablation is still unknown, but the most common symptom is recurrent abnormal bleeding and the state of cancer diagnosed is advanced in many of the cases described [14,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EC after endometrial ablation is a rare but possible occurrence, as described in the literature in a number of case reports [13][14][15][16][17][18][19][20][21][22]. The exact rate of EC after endometrial ablation is still unknown, but the most common symptom is recurrent abnormal bleeding and the state of cancer diagnosed is advanced in many of the cases described [14,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The exact rate of EC after endometrial ablation is still unknown, but the most common symptom is recurrent abnormal bleeding and the state of cancer diagnosed is advanced in many of the cases described [14,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Istre et al [10] showed that an estrogen therapy alone led to a higher number of hyperplasias and should be avoided. A preoperative exclusion of hyperplasia is important, because the development of endometrial carcinoma can be short [11,12]. After endometrial ablation the diagnostics of the corpus carcinoma can be difficult because the cavity is obliterated [13].…”
Section: Discussionmentioning
confidence: 99%